Using Design Thinking to Design an Application for Recognizing the Work of IT Professionals - Lima, Juliana; Simões, Adriano; Vieira, Andréia; Braga, Luis Carlos da Silva; Ferreira, Bruna Moraes (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
The quality of the development process depends not only on the methodologies and on techniques employed, but also on the people who participate in this process. In this context, motivation is an important aspect because it affects the productivity of IT professionals and on the quality of the software developed. A factor that can negatively influence motivation is the lack of recognition for the work done. In the long term, lack of recognition can lead to demotivation and low performance in activities. In order to understand the perception and expectations of IT professionals regarding the recognition of work, a Design Thinking process was carried out. This process focuses on understanding problems based on human expectations and needs in an especific context and generating solutions based on this understanding. This paper reports the experience of using Design Thinking to support the design of a tool for recognition of work in software companies. During the project, we carried out a research with 30 IT professionals from two software companies; we proposed the idea of the tool and conducted tests with possible users. Based on the results of the process, we developed the LIKE tool, aiming to increase the visibility of the contributions of the professionals, facilitate their recognition among colleagues; make explicit knowledge by recording feedback and providing rewards.